How Does Sub-National Autonomy Affect the Effectiveness of Structural Funds? - Cornelius Baehr (European Regional Science Association (ERSA), 2006)
Economic and social cohesion between the EU Member States is one of the explicitly stated goals in the Treaty on European Union. The EU's Structural Funds as a part of the Union's regional policies are a mechanism of conditional grants that provides co-financing for growth enhancing investments. Evidence on the effectiveness of the Structural Funds is mixed. While Boldrin and Canova (2001) find no sign of a catch-up effect of regions receiving aid for the period of 1980-1996, Beugelsdijk and Eijffinger (2005) find a positive relationship between (lagged) Structural Funds expenditure and GDP growth at the national level covering 1995-2001. De La Fuente (2002) points to the fact that the inclusion of conditioning variables might also play a crucial role for the results. Ederveen, deGroot and Nahuis (2002) find that Structural Funds themselves have a negative impact on growth. However, the impact turns out to be significantly positive, when interacting variables measuring institutional quality are taken into account. Similarly, Esposti (2005) shows that additional policy measures (spending on CAP) can have significant counter-effects on the effectiveness of Structural Funds expenditure. So far the federal structure of the EU Member States did not attract much attention when the effectiveness of the Structural Funds is considered. Although the EU Commission requires the inclusion of regional authorities and stakeholders in the planning and implementation procedure of programs funded by Structural Funds, one should expect that the performance is better, where the sub-national authorities are more accustomed to pursuing economic policy and implementing programs. This should be the case in states with a higher degree of sub-national autonomy. Using panel-data for a sample of 13 EU Member States from 1960-1995 the effects of Structural Funds on growth are analysed. Then a decentralization index by Stegarescu (2004) is introduced as an interacting variable in order to measure the degree of sub-national autonomy. This paper shows that increasing sub-national autonomy has a significantly positive impact on the effectiveness of the Union's Structural Funds expenditure.
Keywords: 330